Lineage-level species distribution model to assess the impact of climate change on the habitat suitability of Boleophthalmus pectinirostris - Wu, Zengman; Dong, Hao; Li, Linjie; Zhao, Linlin; Song, Na (Frontiers in Ecology and Evolution, 2024)
Global climate change has profound impacts on the habitats of marine organisms. Therefore, predicting the habitat changes of species under climate change conditions is crucial for species sustainability. Boleophthalmus pectinirostris (Linnaeus, 1758, Gobioidei, Gobiidae) is an intertidal fish species that holds significant ecological and economic value. To better protect and manage its resources, this study predicted its current potential distribution and habitat changes under different climate scenarios in the future. This study first quantified the hypervolume niches of the three lineages (AE1, AE2, and AES lineages) and compared the niche differentiation among them. The results indicated marked ecological niche differentiation among the three lineages. Furthermore, this study constructed species-level and lineage-level species distribution models to assess the impact of climate change on the habitat suitability of B. pectinirostris. The response of different lineages to environmental variables was different, indicating that lineage-level models may provide more accurate prediction results. According to the model predictions, the AES may have greater resilience to climate change and may experience habitat expansion in the future, while the AE1 and the AE2 may face habitat loss in some regions. The results of this study will provide important information for the future management and conservation of the species resources.